Penerapan Training Multi Divisi dalam Menghadapi Keterbatasan Karyawan - Nia Nadilla; Selvi Yona Sari; Selvi Zola Fenia (CV. ITTC INDONESIA, 2026)
The shortage of human resources has become one of the major challenges faced by organizations in maintaining operational effectiveness and service quality. Companies with a limited workforce are required to optimize employee competencies through adaptive and sustainable development programs. This community service activity aimed to improve employee flexibility and work effectiveness by implementing multi-division training. The program was conducted using participatory methods, including needs assessment, training implementation, simulations, mentoring, and evaluation. Employees were equipped with cross-functional competencies, enabling them to understand and perform basic tasks across different divisions. The evaluation results indicated improvements in employees' knowledge, technical skills, teamwork, communication, and adaptability. Furthermore, participants demonstrated increased confidence in handling additional responsibilities during workforce shortages. The implementation of multi-division training proved to be an effective strategy in enhancing organizational resilience, improving operational efficiency, and preparing employees to face dynamic work environments. Therefore, organizations are encouraged to integrate cross-functional training into their human resource development strategies to support sustainable organizational performance.